Correlations between disease-specific and generic health status questionnaires in patients with advanced COPD: a one-year observational study - Wilke, Sarah (BioMed Central, 2012)
BACKGROUND: Longitudinal studies analyzing the correlations between disease-specific and generic health status questionnaires at different time points in patients with advanced COPD are lacking. The aim of this study was to determine whether and to what extent a disease-specific health status questionnaire (Saint George’s Respiratory Questionnaire, SGRQ) correlates with generic health status questionnaires (EuroQol-5-Dimensions, EQ-5D; Assessment of Quality of Life instrument, AQoL; Medical Outcomes Study 36-Item Short-Form Health Survey, SF-36) at four different time points in patients with advanced COPD; and to determine the correlation between the changes in these questionnaires during one-year follow-up. METHODS: Demographic and clinical characteristics were assessed in 105 outpatients with advanced COPD at baseline. Disease-specific health status (SGRQ) and generic health status (EQ-5D, AQoL, SF-36) were assessed at baseline, four, eight, and 12 months. Correlations were determined between SGRQ and EQ-5D, AQoL, and SF-36 scores and changes in these scores. Agreement in direction of change was assessed. RESULTS: Eighty-four patients (80%) completed one-year follow-up and were included for analysis. SGRQ total score and EQ-5D index score, AQoL total score and SF-36 Physical Component Summary measure (SF-36 PCS) score were moderately to strongly correlated. The correlation of the changes between the SGRQ total score and EQ-5D index score, AQoL total score, SF-36 PCS, and SF-36 Mental Component Summary measure (SF-36 MCS) score were weak or absent. The direction of changes in SGRQ total scores agreed slightly with the direction of changes in EQ-5D index score, AQoL total score, and SF-36 PCS score. CONCLUSIONS: At four, eight and 12 months after baseline, SGRQ total scores and EQ-5D index scores, AQoL total scores and SF-36 PCS scores were moderately to strongly correlated, while SGRQ total scores were weakly correlated with SF-36 MCS scores. The correlations between changes over time were weak or even absent. Disease-specific health status questionnaires and generic health status questionnaires should be used together to gain complete insight in health status and changes in health status over time in patients with advanced COPD.